2021
DOI: 10.1186/s12872-021-01995-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental parameters and infarct size in closed chest pig LAD ischemia reperfusion models; lessons learned

Abstract: Background Preclinical models that resemble the clinical setting as closely as possible are essential in translating promising therapies for the treatment of acute myocardial infarction. Closed chest pig left anterior descending coronary artery (LAD) ischemia reperfusion (I/R) models are valuable and clinically relevant. Knowledge on the influence of experimental design on infarct size (IS) in these models is a prerequisite for suitable models. To this end, we investigated the impact of several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…We report on the longitudinal structural changes that affect the infarcted myocardium and show that at 42 days post‐STEMI, scar size is comparable among pigs subjected to 60 min or longer and smaller than that observed on day 3. Previous studies in closed‐chest pig LAD ischemia/reperfusion have also shown that increasing occlusion times result in an increased infarct size (expressed per AAR) reaching a plateau, and ischemia times longer than 2 h have not shown to lead to larger infarcts as compared to persistent coronary occlusion 18,20 . Notably, CMR was not available in these studies.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…We report on the longitudinal structural changes that affect the infarcted myocardium and show that at 42 days post‐STEMI, scar size is comparable among pigs subjected to 60 min or longer and smaller than that observed on day 3. Previous studies in closed‐chest pig LAD ischemia/reperfusion have also shown that increasing occlusion times result in an increased infarct size (expressed per AAR) reaching a plateau, and ischemia times longer than 2 h have not shown to lead to larger infarcts as compared to persistent coronary occlusion 18,20 . Notably, CMR was not available in these studies.…”
Section: Discussionmentioning
confidence: 85%
“…They reported no significant differences in infarct size expressed as the risk area between animals banded for 60 min or above, supporting the need to reperfuse within 1 h after occlusion. In a study in a closed‐chest model of balloon‐induced MI, Silvis et al 20 evaluated the impact of 60, 75 and 90 min of ischemia followed by 24 h reperfusion in thiopental anaesthetised pigs. No differences were observed in the AAR as % LV between the different occlusion groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, pigs were exposed to prolonged ischemia times and the mice were subjected to permanent ligation. By comparing 60, 75 and 90 min occlusion in the closed chest LAD ligation model in pigs it was recently shown that increasing occlusion times lead to significantly larger infarct sizes, with almost complete transmural infarcts upon 90 min occlusion time (Silvis et al, 2021) In the current study, we used a porcine model of severe IR injury with 150 min occlusion time and a mice model of permanent myocardial infarction. Consequential to the prolonged ischemia time the damage is presumably in an irreversible state, thereby limiting the therapeutic benefit on salvaging myocardial ischemiareperfusion-related injury.…”
Section: Discussionmentioning
confidence: 99%